Complete plastome of Houttuynia cordata (Saururaceae), a medicinal and edible plant. Issue 2 (3rd July 2019) - Jin, Lei; Yang, Jin; Liu, Changkun; He, Mengling; Yan, Hanjing
Abstract: The complete plastome of Houttuynia cordata, an important medicinal and edible plant, was identified and sequenced in this study. The circular plastome is 160, 217 bp in length and consists of a pair of inverted repeats (IRs 26, 854 bp each), which is separated by a large single-copy region (LSC, 88, 189 bp) and a small single-copy region (SSC, 18, 320 bp). It encodes 132 genes, of which 114 are unique genes (80 protein-coding genes, 30 tRNAs, and 4 rRNAs). The phylogenetic analysis strongly reveals the sister group between H. cordata and the clade including Piper kadsura, Piper cenocladum, Saruma henryi, and Asarum sieboldii .